1986
DOI: 10.1128/aem.52.1.200-202.1986
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Oxygen from Water into Toluene and Benzene during Anaerobic Fermentative Transformation

Abstract: Toluene and benzene were anaerobically transformed and eventually mineralized in mixed methanogenic cultures. However, the source of oxygen for the initial oxidation step had been unknown, owing to the presence of both methanol and water. No exogenous electron acceptors other than carbon dioxide, toluene, and benzene were present in the defined mineral medium. Through the use of 180-labeled water, the oxygen incorporated into the monoaromatic compounds was shown to come from water. The cresol from the toluene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(108 citation statements)
references
References 8 publications
3
104
0
1
Order By: Relevance
“…Other compounds sought (based on presumed degradation pathways) but not detected included benzaldehyde, 2-, 3-and 4-methylcyclohexanol, catechol (1, 2-dihydroxybenzene), methylcatechol, resorcinol (1, 3-dihydroxybenzene), methylresorcinol, 2-, 3-and 4-hydroxybenzoate, 2-, 3and 4-hydroxybenzylalcohol, and gentisate. Although hydroxylated intermediates have been previously identified during methanogenic toluene degradation (Vogel and Grbic'-Galic', 1986), they may also be produced during aerobic biodegradation (Gibson and Subra-manian, 1984). Recent reports showed that hydroxylated compounds may be formed abiotically during sample processing (Kunapuli et al, 2008).…”
Section: Compounds Detected During Methanogenic Toluene Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Other compounds sought (based on presumed degradation pathways) but not detected included benzaldehyde, 2-, 3-and 4-methylcyclohexanol, catechol (1, 2-dihydroxybenzene), methylcatechol, resorcinol (1, 3-dihydroxybenzene), methylresorcinol, 2-, 3-and 4-hydroxybenzoate, 2-, 3and 4-hydroxybenzylalcohol, and gentisate. Although hydroxylated intermediates have been previously identified during methanogenic toluene degradation (Vogel and Grbic'-Galic', 1986), they may also be produced during aerobic biodegradation (Gibson and Subra-manian, 1984). Recent reports showed that hydroxylated compounds may be formed abiotically during sample processing (Kunapuli et al, 2008).…”
Section: Compounds Detected During Methanogenic Toluene Metabolismmentioning
confidence: 99%
“…Earlier investigations examining toluene biodegradation under methanogenic conditions have also implicated metabolites such as o-cresol, o-methylcyclohexanol, p-cresol, p-methylcyclohexanol, methylcyclohexane, 2-hydroxybenzoate, benzylalcohol, benzaldehyde and benzoate (Grbic'-Galic' and Vogel, 1987), suggesting that alternative mechanisms of toluene activation in the absence of endogenous electron acceptors, such as ring or methyl group hydroxylation, may be possible. In studies using 18 O-H2O, Vogel and Grbic'-Galic' (1986) showed the incorporation of an 18 O atom into toluene forming labelled p-cresol, demonstrating that hydroxylation may also occur under methanogenic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Methyl substituents of the aromatic ring are difficult to attack in the absence of molecular oxygen, which normally initiates degradation. Methylated aromatic compounds, that are readily degraded anaerobically include toluene (Vogel and Grbic-Galic, 1986;Wilson et al, 1986;Zeyer et al, 1986;Dolfing et al, 1990: Lovley andLonergan, 1990;Schocher et al, 1991 ;Rabus et al, 1993;Fries et al, 1994: Rueter et al, 1994 and the ortho, rnetu and para isomers of xylene (Zeyer et al, 1986;Evans et al, 1991Evans et al, , 1992Seyfried et al, 1994;Edwards and Grbic-Galic, 1994;Rueter et al, 1994;Haner et al, 1995) and of cresol (Lovley and Lonergan, 1990;Hopper et al, 1991 ;Rudolphi et al, 1991 ;Flyvbjerg et al, 1993;Bonting et al, 1995). At least two different pathways can be used for the first attack under anaerobic conditions.…”
Section: Reductive Dehalogenationmentioning
confidence: 99%
“…Anaerobic benzene degradation has been described in several publications with nitrate, sulfate and ferric iron as electron acceptors in microcosms and enrichments (Vogel and Grbic-Galic, 1986;Edwards and Grbic-Galic, 1992;Lovley et al, 1994;Phelps et al, 1996;Kazumi et al, 1997;Burland and Edwards, 1999;Lovley, 2000;Zwolinski et al, 2000;Jahn et al, 2005;Kunapuli et al, 2007). Even methanogenic cultures are known (Vogel and Grbic-Galic, 1986;Ulrich et al, 2005) and two denitrifying pure cultures degrading benzene have been described (Coates et al, 2001a;Kasai et al, 2006). However, there is still no definitive study on the nature of the activation mechanism.…”
Section: Introductionmentioning
confidence: 99%